13th North American Caribou Workshop, 25-28 October 2010, Winnipeg, Manitoba, Canada. - Haugerud (editor in chief), Rolf Egil; Manseau (issue editor), Micheline; Simmons, Deborah; Brannen, Dennis; Crichton, Vince; Ryckman, Mark; Elliott (issue associate editors), Jessica (Rangifer, 2012)
The 13th North American Caribou Workshop which was held in Winnipeg, Manitoba, was a great success with more than 400 participants: people from Canada, the United States, Norway and Greenland, representatives from co-management and resource management boards across North America, First Nations, Inuit and Inuvialuit, governmental and non-governmental organisations, private companies, researchers, students and youth. The theme of the Workshop was Sustaining Caribou and their Landscapes – Knowledge to Action and the intent of the organizers was twofold: first, to provide participants with the opportunity to share scientific and traditional knowledge on different subspecies and ecotypes of Rangifer across the circumpolar North, the particularities of the different landscapes and land use management issues; second, to explore innovative ways to transfer knowledge to action, ensuring the long-term persistence of Rangifer throughout its range through the development of better governance structures, sound policies and effective communication.